A History of World Societies to 1600 : volume 1 - Wiesner, Merry E.; Ebrey, Patricia Buckley; Beck, Roger B.; Dávila, Jerry; Crowston, Clare Haru; MacKay, John P. (Bedford/Saint Martin's, 2019)
Insert Front Cover -- About the Cover Image -- Maps -- Half-title Page -- Title Page -- Copyright Page -- Preface -- Versions and Supplements -- Brief Contents -- Contents -- Maps, Figures, and Tables -- Chapter 1: The Earliest Human Societies, to 2500 B.C.E. -- Evolution and Migration -- Understanding the Early Human Past -- Hominid Evolution -- Homo Sapiens, "Thinking Humans" -- Migration and Differentiation -- Later Paleolithic Society, ca. 200,000-9000 B.C.E. -- Foraging for Food -- Family and Kinship Relationships -- Cultural Creations and Spirituality -- The Development of Agriculture in the Neolithic Era, ca. 9000 B.C.E. -- The Development of Horticulture -- Animal Domestication and the Rise of Pastoralism -- Plow Agriculture -- Neolithic Society -- Social Hierarchies and Slavery -- Gender Hierarchies and Inheritance -- Trade and Cross-Cultural Connections -- Chapter Summary -- Connections -- Chapter 1 Review -- Chapter 2: Complex Societies in Southwest Asia and the Nile Valley, 3800-500 B.C.E. -- Writing, Cities, and States -- Written Sources and the Human Past -- Cities and the Idea of Civilization -- The Rise of States, Laws, and Social Hierarchies -- Mesopotamia from Sumer to Babylon -- Environmental Challenges, Irrigation, and Religion -- Sumerian Politics and Society -- Writing, Mathematics, and Poetry -- Empires in Mesopotamia -- Life Under Hammurabi -- The Egyptians -- The Nile and the God-King -- Egyptian Society and Work -- Migrations, Revivals, and Collapse -- Iron and the Emergence of New States -- The Hebrews -- The Hebrew State -- The Jewish Religion -- Hebrew Society -- The Assyrians and the Persians -- Assyria, the Military Monarchy -- The Rise and Expansion of the Persian Empire -- The Religion of Zoroaster -- Chapter Summary -- Connections -- Chapter 2 Review -- Chapter 3: The Foundation of Indian Society, to 300 C.E.